THE IMPORTANCE OF ENGLISH COMMUNICATION SKILLS FOR ACCOUNTING STUDENTS IN THE ERA OF ARTIFICIAL INTELLIGENCE - Cristian Nainggolan; Lisbet Manalu (Merwin Publisher, 2026)
This study aims to analyze the importance of English communication skills for accounting students in the era of artificial intelligence. The development of artificial intelligence has changed accounting education and professional practice, especially in financial reporting, data analysis, auditing, and the use of digital accounting tools. In this context, accounting students need English communication skills to support their academic understanding and professional readiness. This study used a qualitative descriptive method with a literature review approach. The data were obtained from relevant previous studies related to English communication skills, accounting education, artificial intelligence, digital accounting, and career readiness. The findings show that English communication skills support accounting students in five main aspects: understanding international accounting terminology, accessing global academic references, using English-based accounting software and AI tools, preparing financial and academic reports, and communicating professionally in global business contexts. The study also indicates that limited English communication competence may reduce students’ ability to adapt to digital and AI-driven accounting practices. Therefore, integrating English communication training into accounting education is necessary to prepare accounting students to become more adaptive, competent, and competitive in future accounting careers.